2011
DOI: 10.1212/wnl.0b013e31823a0ef7
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-level comparison of arterial spin-labeled perfusion MRI and FDG-PET in Alzheimer disease

Abstract: Objective:We compared the ability of arterial spin labeling (ASL), an MRI method that measures cerebral blood flow (CBF), to that of FDG-PET in distinguishing patients with Alzheimer disease (AD) from healthy, age-matched controls.Methods: Fifteen patients with AD (mean age 72 Ϯ 6 years, Mini-Mental State Examination score[MMSE] 20 Ϯ 6) and 19 age-matched controls (mean age 68 Ϯ 6 years, MMSE 29 Ϯ 1) underwent structural MRI. Participants were injected with 5 mCi of FDG during pseudocontinuous ASL scan, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
188
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(207 citation statements)
references
References 40 publications
19
188
0
Order By: Relevance
“…Our results are consistent with prior work, which showed that regional CBF is tightly coupled with regional cerebral metabolic rate for glucose,51 and that patterns of regional perfusion abnormalities are very similar to the patterns of hypometabolism in AD 27. In addition, prior studies have indicated that the diagnostic value of ASL‐MRI is similar to that of FDG‐PET in AD 25, 26.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with prior work, which showed that regional CBF is tightly coupled with regional cerebral metabolic rate for glucose,51 and that patterns of regional perfusion abnormalities are very similar to the patterns of hypometabolism in AD 27. In addition, prior studies have indicated that the diagnostic value of ASL‐MRI is similar to that of FDG‐PET in AD 25, 26.…”
Section: Discussionsupporting
confidence: 92%
“…Despite these limitations, the practical clinical implications of this report add to other reports25, 26, 27 suggesting that ALS‐MRI has a similar sensitivity and specificity to FDG‐PET for detecting brain changes due to AD and bvFTD. MRI examinations are noninvasive without ionizing radiation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…21,22 HMPAO SPECT and FDG-PET showed hypoperfusion and decreased metabolism in the temporoparietal and posterior cingulate gyrus in AD, which indicates a direct coupling in AD between these 2 effects. 23 In addition, a recent study to compare 3D ASL MR imaging with FDG-PET in the same subjects showed similar degrees of functional deficits in the affected areas, 24 which indicates that 3D ASL MR imaging may be a more easily accessible alternative perfusion technique than SPECT in the diagnosis of AD.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, studies using arterial spin labeling, an MRI technique that measures blood flow through arterioles and capillaries, have found cerebral hypoperfusion in patients with mild MND [13]. Interestingly, the same areas of cerebral hypoperfusion found on arterial spin labeling demonstrated hypometabolism on 18 F-2-flouro-2-deoxy-Dglucose (FDG)-PET images [13,14]. Chronic NVU, as seen in MND, can hasten neurodegeneration via several proposed processes including neuroinflammation and oxidative stress induction with associated amyloid beta (Aβ) deposition, tau hyperphosphorylation, and synaptic malfunction leading to eventual neuronal injury [10,[15][16][17][18].…”
Section: Functional Task Batterymentioning
confidence: 99%